Cognitive effects of heading in professional football: a systematic review - Patel, L.; Tarafder, J.; Ronca, F. (International Journal of Sports Medicine, 2024)
Large cohort studies have reported that former professional football players have an increased risk of mortality from neurodegenerative disease. Due to emerging concerns regarding the safety of heading the technique is now banned for players under 12. The aim of this systematic review was to evaluate the association between heading exposure and cognitive function in professional football players. A search strategy was devised and entered into seven electronic databases: MEDLINE, Embase, Web of Science, PsycINFO, CENTRAL, SportDiscus and PEDro. The search identified 563 records. After screening records and applying the eligibility criteria, nine cross-sectional studies (n=925) were included in the review, investigating 452 current and 473 former players (859 males, 66 females). Six studies (n=595) reported evidence for an association between heading and impaired cognitive function, while three studies (n=330) reported no association. Diverse cognitive domains were investigated, which might underline the disparity in these results. The association between heading and cognitive function in professional football appears likely but remains inconclusive. Methodological heterogeneity and variability in the presentation of results limits the conclusions drawn. Prospective longitudinal studies using standardised methods, and including females, are required to provide evidence to support or refute an association.